Provisions for old age. Income provisions and retirement - Tatjana Mika; Uwe Rehfeld; Michael Stegmann (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
Research on the income situation of todays and future retirees requires often record based data. Because of their accuracy in the life-course infomation they can also, if they are linked to survey data, make interviews shorter and less demanding for the interviewed persons. Process produced data from the pension fund are already available for these research topics. The data include details about the employment career and other life-course events as far as they are considered in the pensions calculation. Nevertheless, additional sources are needed if research projects address the income situation more in detail, in particular the question of poverty or high income in old age. The pension reforms of the past decade have strengthened the second and third pillar in the importance, thereby increasing their importance of occupational pensions and private savings for future old age income. There exist already some detailed and inclusive data for research on old age income and retirement collected for government reports, but not all this data is yet available for scientific research. Furthermore should the exchange of data between social securitiy and/or tax institutions more often be combined with the collection of statistical data in order to improve the possibility of record-to-record linkage.
Keywords: 330; Retirement; old age provisions; public pension fund; process produced data; data linkage